Cluster-based key management scheme for ad hoc networks - HU Rong-lei1 2; LIU Jian-wei2; ZHANG Qi-shan2 (Tongxin xuebao)
A new threshold key distribution scheme basing on self-certified public key and CPK（composite public key） technology was presented for ad hoc networks.Basing on the key distribution scheme and cluster networks structure,an integrated key management scheme was presented.The public key can be certified itself and so the certificate is not need in the scheme.The process of key distribution is simple and the key escrow problem existing in IBE（identity-based en-cryption） scheme is solved.The scheme can be used in different scale networks and can meet the dynamic topology of the ad hoc networks.The experimental results and theoretical analysis show that the overhead of computation and communi-cation is lower.Comparing with PKI and IBE scheme the scheme is more secure and practical.